A View of Oral Communication Activities in Food Science From the Perspective of a Communication Researcher. Issue 2 (April 2015) - Ann Vrchota, Denise
Abstract: Food science researchers have pronounced the Institute of Food Technologists Success Skills to be the most important competency mastered by graduates entering the work force. Much of the content and outcomes of the Success Skills pertains to oral communication skills of public speaking and interpersonal and group communication. This qualitative study reports the results of an examination of oral communication activities in the classes of 9 faculty in the food science program at Iowa State Univ. The findings revealed communication activities in the classes that support the Success Skills oral communication mandates; however, the food science faculty did not explicitly teach these skills. Faculty assumed the students would acquire proficiency in oral communication through participation in disciplinary activities that required them to practice the skills. A situated communication framework cautions communication researchers to honor the oral communication traditions in other disciplines. Still, the practice of preparing students to communicate in professional contexts without formal instruction raises 2 questions from the perspective of a communication researcher: first, are students aware of the communication skills they applied in classroom activities? Second, are students able to transfer communication skills to other classes and, more importantly to professional practice, when they graduate, as a result of this approach? The discussion suggests exercises that direct students' attention to the specific skill sets inherent in the oral communication activities in the Success Skills while enabling faculty to maintain the communication traditions of food science as they prepare students for professional practice.